Risk Factors of Disease Progression After Cataract Surgery in Chronic Angle-closure Glaucoma Patients. Issue 4 (April 2016) - Lee, Chang Kyu; Lee, Na Eun; Hong, Samin; Kang, Eunmin; Rho, Seung Soo; Seong, Gong Je; Hong, Young Jae; Kim, Chan Yun
Abstract : Purpose: To evaluate clinical risk factors of disease progression after cataract surgery using phacoemulsification with posterior chamber intraocular lens implantation, in eyes with chronic angle-closure glaucoma (CACG) and coexisting cataract. Design: Retrospective study. Methods: The data of 56 eyes of 45 CACG patients who had undergone uncomplicated phacoemulsification with posterior chamber intraocular lens implantation were retrospectively analyzed. Disease progression was defined as glaucomatous optic nerve change or visual field (VF) deterioration according to the European Glaucoma Society guideline. Correlations between VF progression and various preoperative and postoperative factors were determined by χ 2 and independent t tests. Linear regression analysis [(odds ratio (OR)] was used to determine predictive risk factors for disease progression using univariate and multivariate analyses. Results: The mean postoperative follow-up period was 45.13±17.54 (24 to 84) months. Fourteen eyes (25%) with cataracts diagnosed with CACG progressed after phacoemulsification, but the remaining 42 eyes (75%) did not. According to univariate analysis, disease progression was significantly associated with older age, more number of preoperative/postoperative antiglaucoma drugs, higher scores of preoperative pattern standard deviation, and lower scores of preoperative and postoperative visual field index (VFI) ( P <0.05). Using multivariate analysis, a lower score of preoperative VFI (OR: 0.86, P =0.044) and lower postoperative intraocular pressure (IOP) reduction, which was not sustained below 20% less than the preoperative mean IOP, were significantly correlated with disease progression after cataract surgery (OR: 8.44, P =0.048). Conclusions: CACG patients with low preoperative VFI and high postoperative IOP are at risk for disease progression even after uncomplicated cataract surgery.